Investigation of Interaction Between Viscosity-modifier Polymers and Surfactants Based on Vegetable Oil for Chemical Enhanced Oil Recovery - Roland Nagy; Máté Hartyányi; László Bartha; Sándor Puskas (Chemical Engineering Transactions, 2024)
Chemical enhanced oil recovery (CEOR) is surely a topic of interest. The process of chemical flooding with solutions of polymers and surfactants can be used for developing oil recovery. The bio-based surfactants have much attention from both scientific and industrial point of views due to their renewable and environment friendly nature and the bio-based surfactants has lower toxicity and better biodegradability. The theory of interactions between polymers and surfactants have been markedly studied. This is particularly important for understanding the mechanism of chemical enhanced oil recovery. The interaction between various surfactant mixtures and flow-modifying polymers in brine solutions was investigated (in practical terms) using various analytical methods, including interfacial tension, emulsification capacity, rheological properties, and oil displacement measurements. Based on the experimental data a significant level of interaction between the surfactants and the polymers were found. It was obtained that by applying flow modifier polymer together with the investigated surfactants the additional oil production could increase.